Pengaruh Kotoran Ternak terhadap Budidaya Bawang Merah (Allium ascalonicum L.) off Season di Kabupaten MBD - Suneth, Risma Fira; Wahid, Wahid; Van Room, Maryeke; Hidayah, Ismatul (Seminar Nasional Lahan Suboptimal, 2020)
Suneth RF, Wahid W, Room MV, Hidayah I. 2020. Effect of manure on off season shallot (Allium ascalonicum L.) cultivation in MBD regency. In: Herlinda S et alÂ  (Eds). Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Organic off-season cultivation of shallots is one way to maintain the availability of shallots. Off-season shallots are a concern to be applied in Southwest Maluku Regency (MBD) in developing shallot centers in dry wet climates. This activity aims to explain the effect of onion cultivation outside the season (off season) using goat manure in the coastal area of Lakor Island, Southwest Maluku Regency. The study was carried out in April - June 2019 Lakor Island, MBD Regency, using a randomized block design consisting of 4 treatments (P) and repeated 4 times. Treatments using manure in the form of fermented livestock manure include P0; Without Manure, P1; pukan 10 ton/ha+ organic supplementary fertilizer, P2; pukan 20 ton/ha+ organic supplementary fertilizer, P3; pukan 30 ton/ha+ organic supplementary fertilizer. The results of the study showed that the treatment of 30 tonnes of fertilizers + organic supplementary fertilizer (P3) gave the best results on growth variables with plant height 34.95 cm, number of tillers 6.07 with the number of tubers 6.84 planting / holes. The harvest variables showed that P3 treatment was better, namely the wet tuber weight of harvested tubers 5.71 tonnes / ha, dry tuber weight 4.42 tonnes/ha. The application of the off season system can help farmers continue to cultivate shallots even in the rainy season.